Detection of erythroid hypoplasia in myelofibrosis using erythrokinetic studies. Issue 12 (December 1989) - Howarth, J E; Waters, H M; Hyde, K; Geary, C G
Abstract : The iron kinetic model described by Ricketts et al was used to study haemopoiesis in chronic myelofibrosis. The clearance of 59Fe-labelled transferrin from the plasma was analysed to quantify total, effective, and ineffective erythropoiesis, denoted by the terms marrow iron turnover (MIT), red cell iron turnover (RCIT), and per cent ineffective iron turnover (IIT%), respectively, in 12 cases of this disease. The patterns obtained were variable: values for MIT ranged from 24.4 to 510 mumol/l blood/day; those for RCIT from 0.4 to 119 mumol/l blood/day; and those for IIT% from 67 to 98%. One noteworthy feature was the presence in two cases of functional erythroid hypoplasia; these were characterised by severely reduced values for MIT (24.4 and 28 mumol/l blood/day) and RCIT (0.4 and 8 mumol/l blood/day.) A systematic study of the erythrokinetic features of myelofibrosis may indicate that erythroid hypoplasia is a more common cause of anaemia in this disease than has been previously recognised.